Uji Antagonis Jamur Trichoderma sp. terhadap Penyakit Antraknosa Colletotrichum sp. pada Tanaman Cabai Keriting Capsicum annuum L. di Laboratorium - Sanothan, Arianti; Montong, Vivi B.; Lengkong, Maxi (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
This study aims to determine the antagonistic test of Trichoderma sp. against anthracnose disease, Colletotrichum sp. on curly chili plants, Capsicum annuum L. The research was conducted using the double culture method which was carried out by placing 5 mm diameter pieces of mycelium of pathogens and antagonists aged 7-9 days each on PDA media in one petri dish. The control treatment was isolated media without antagonistic fungi. The results showed that Trichoderma sp. fungi can perform space and nutrient competition against Colletotrichum sp. fungi macroscopically by controlling space and nutrients and microscopically by competition, microparasitism and antibiosis. The percentage of inhibition of antagonistic fungi Trichoderma sp. against Colletotrichum sp. fungi increased every day and on day 7 could reach 100%. Keywords: Curly Chili, Trichoderma sp., Colletotrichum sp., in-vitro